PERAN PUBLIC RELATIONS DALAM MENGINFORMASIKAN JASA PELAYANANPT POS INDONESIA (PERSERO) KEDIRI - Erwin Syahputra (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2017)
Every firm always focus on their existing services product and also introducing the new products, in which public relations has an important role. The research aims to analyze the role of public relations in informing the public about the new and existing services products of PT. Pos Indonesia (Persero) Kediri. 50 respondents selected accidentally to fill the questionaires. The results identified the unsatisfied role of public relations section in the corporate to inform and/or introduce the services products offered on public. In the case, a lot of customers still not aware the offered products.